Moderation effect of gender on relationship between community of inquiry and perceived learning in blended learning environments - Khodabandelou, Rouhollah; Ab. Jalil, Habibah; Wan Ali, Wan Zah; Mohd Daud, Shaffe (Contemporary Educational Technology, 2014)
It is conceivably important that demographic variables such as gender may have an impact on community of inquiry (CoI) and perceived learning. This study is in response with Garrison et al. (2010) who suggest that there is a need to determine moderation effects of gender on the relationship between CoI elements and perceived learning. A total of 348 undergraduate students were drawn from blended programs in three public universities in Malaysia to be the sample of the study. As research instrumentation, participation in online and face to face session, the community of inquiry questionnaire, and a perceived learning scale were distributed among the respondents. All the questionnaires were validated by a panel of experts, reliability of the instrument was tested in a pilot study and assumptions of Structural Equation Modeling (SEM) were checked before analyzing the data. The findings of the study have shown that although differences between the two groups of undergraduate students (male and female) were statistically significant, the amount of differences were not enough to moderate the relationship between CoI components and perceived learning in undergraduate blended learning environments. However, the findings indicate that differences between the two groups of undergraduate students (male and female) were statistically significant.